2021
DOI: 10.2991/jegh.k.210524.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Microbiological Profile of Common Healthcare Associated Infections among Patients in the Intensive Care Unit of a General Hospital in Kuwait: A Retrospective Observational Study

Abstract: Background: Patients admitted to the Intensive Care Unit (ICU) are prone to develop nosocomial infections due to Multidrug-Resistant (MDR) organisms. Inappropriate and overuse of antibiotics play an important role in the emergence of MDR organisms, which cause life-threatening infections resulting in significant morbidity and mortality. Methods:Retrospective surveillance-based study on healthcare-associated infections. The study conducted over two consecutive years 2018 and 2019, looking at ICU related infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
16
0
3
Order By: Relevance
“…A. baumannii is able to cause both urinary tract infections (UTIs) and asymptomatic bacteriuria in both hospital and community settings ( 22 ). Several individual center studies report that A. baumannii is one of the most common uropathogens causing CAUTI in their facility ( 23 , 24 ). In addition, about one-fifth of A. baumannii clinical strains are isolated from the urine of patients suffering from UTIs ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…A. baumannii is able to cause both urinary tract infections (UTIs) and asymptomatic bacteriuria in both hospital and community settings ( 22 ). Several individual center studies report that A. baumannii is one of the most common uropathogens causing CAUTI in their facility ( 23 , 24 ). In addition, about one-fifth of A. baumannii clinical strains are isolated from the urine of patients suffering from UTIs ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…These patients usually suffer from severe underlying diseases and routine invasive procedures, which are commonly associated with the occurrence and mortality of CRPA infections in many studies ( 14 , 15 ). The incidence of infection in ICU patients is five–seven-fold higher than that in general inpatients, contributing to 20%−25% of all nosocomial infections in hospitals ( 16 ). It is important to timely identify risk factors for CRPA infection to prompt an effective intervention strategy to prevent the development of CRPA.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Ethiopia showed that Gram-negative bacteria were isolated from 8.3% of HCWs’ mobile phones and 79.4% of the isolates were multidrug resistant [ 31 ]. Antibiotic-resistant bacteria are the most serious health risk for hospitalized patients [ 32 ]. Besides, Enterococcus faecium and E. coli were isolated from mobile phones in this study, which suggested poor hygiene conditions of mobile phones and hands because these bacteria are part of the intestinal flora.…”
Section: Discussionmentioning
confidence: 99%